Perfectionism, Stress, and the Entry-Level Doctor of Physical Therapy Student: A Cross-Sectional, Observational Study. Issue 1 (8th March 2022) - Richardson, Michael V.; Miller, Haylie; Papa, Evan; Santurri, Laura
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Perfectionism consists of high standards and hypercritical self-evaluation. Some doctor of physical therapy (DPT) students experience increased stress levels due to rigorous academic expectations. There is limited understanding of how successful these students are at managing increased stress, especially among perfectionists. The purpose was to examine perfectionism among entry-level DPT students and its relationship to perceived stress. Review of Literature: Researchers have studied perfectionism and stress in health professions programs, but not DPT programs. Being a Maladaptive Perfectionist (MP) was positively and strongly associated with stress among health professions students. Subjects: Convenience sample of first-year, second-year, and third-year DPT students ( n = 163). Methods: This was a nonexperimental, single-site, cross-sectional study. Investigators used 3-way analysis of variance to compare student characteristics and binomial logistic regressions to determine whether characteristic and/or perceived stress was predictive of perfectionism subtype. They completed bivariate correlations to determine associations between perfectionism and stress. Results: Sample results demonstrated 41.10% Adaptive Perfectionists and 25.15% MPs. There was a moderate, direct association between perceived stress and the perfectionism discrepancy measure ( r s = .51, P < .01). The perceived stress and perfectionism subtype logistic regression model was statistically significant, χ 2 (1) = 18.73, P < .01. Participants with increased perceived stress had 1.17 times higher odds of being categorized as an MP than those with lower stress levels. Discussion and Conclusion: Maladaptive Perfectionist students may be at greater risk for stress-related issues. Perfectionism and stress measures may assist educators in identifying at-risk students, monitor student response to stress management interventions, and consider curricular changes to lower stress. Students who effectively manage stress may ultimately have overall greater well-being.